An Approach to Intelligent Road Lighting System with Renewable Energy Based Power Supply. (2016) - Ronay, Karoly; Dumitru, Cristian Dragos
Abstract: This paper presents the approach and study of an intelligent electrical consumer, in the analyzed case a road lighting system, powered by renewable energy sources, to achieve energy efficiency. The consumer is equipped with sensors, controlled by a microcontroller unit and can autonomously working. If one of the main objectives is to achieve a better energy efficiency for the electrical consumer, the supply from a renewable energy source makes the consumer environmental friendly. The first aspect of the study is to present the lighting system and the working principle. The LED based lighting modules represents in the modern days the most efficient and reliable lighting system. The renewable energy power system is based on a solar photovoltaic system and represents an alternative supplying way for the lighting systems. Between these two systems, the lighting and the power supply system, a command and control unit has to operate to ensure an accurate system management. The command and control unit has to monitor the available or stored energy from the solar PV system, to read the sensors values that supervise the environment and traffic behavior, and to command the switching of the lighting system for an optimal lighting level and for energy efficiency.